1996
DOI: 10.1007/pl00014234
|View full text |Cite
|
Sign up to set email alerts
|

Decreased bone mineralization in children with phenylketonuria under treatment

Abstract: Children with phenylketonuria (PKU) obtain a great deal of their protein and mineral intakes from synthetic elemental formulae devoid of phenylalanine. To assess the effect of such diets and/or the disease on bone mineralization, children with PKU were compared to normal children for many parameters of mineral homeostasis and bone mineralization. A total of 11 children with PKU of mean age 10.9 +/- 4.2 years were compared to a large group of normal control children mean age 11.4 +/- 4.2, and an age and sex mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
83
0
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(95 citation statements)
references
References 7 publications
7
83
0
5
Order By: Relevance
“…Perez-Duenas et al [6] observed the same levels of OC and BALP in a group of younger patients and significantly lower serum BALP activity in older subjects (>18 years of age). Hillman et al [4] reported results, similar to ours, that bone formation markers (BALP, OC) were significantly lower in prepubertal PKU patients than in controls. Our results concerning the formation as well as resorption markers suggest a decreased bone turnover rate in prepubertal children with PKU compared to controls.…”
supporting
confidence: 89%
“…Perez-Duenas et al [6] observed the same levels of OC and BALP in a group of younger patients and significantly lower serum BALP activity in older subjects (>18 years of age). Hillman et al [4] reported results, similar to ours, that bone formation markers (BALP, OC) were significantly lower in prepubertal PKU patients than in controls. Our results concerning the formation as well as resorption markers suggest a decreased bone turnover rate in prepubertal children with PKU compared to controls.…”
supporting
confidence: 89%
“…Other studies also find no correlations between dietary calcium, protein, and energy intake and BMD, BMD Z-score or BTM in patients of any age (Carson et al 1990;McMurry et al 1992;Hillman et al 1996;Modan-Moses et al 2007;Lage et al 2010). Positive correlations have been reported, however, between total calcium and phosphorus intake and BMD Z-score (PerezDuenas et al 2002) and calcium and protein from medical food and spine BMD (Geiger et al 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Hilman et al 21 , para avaliar os efeitos da dieta na mineralização óssea, compararam crianças portadoras de fenilcetonúria com crianças normais sob alguns parâmetros de homeostase mineral e mineralização ósseos. Onze crianças PKU foram comparadas com crianças normais.…”
Section: Classificaçãounclassified